Dampak Pola Asuh Orangtua Terhadap Perkembangan Anak Usia Dini 4-5 Tahun - Lesnussa, Grishela Chlaudia; Wijayaningsih, Lanny (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Parental parenting styles play a very important role in children's lives because the application of parental parenting styles to children will have an impact on the child's development in behaving in the social environment around him. For this reason, it is necessary to choose the right parenting style in educating, especially within the family environment. However, in an era like this, it is rare to find parents who care about children's development, even though children have more time at home with their parents, this is due to a lack of communication between parents and children, there is no time between parents and children to gather together, parents spend more time to work, lack of control and supervision from parents, parents get children used to playing with cellphones, parents pay less attention to children in learning so children don't know numbers and alphabets, knowledge factors about parenting patterns that parents don't understand. This research aims to find out whether parental parenting patterns can influence the development of early childhood children aged 4-5 years at PGRI Kokroman Kindergarten, What is the impact of parental parenting patterns on the development of early childhood children 4-5 years old at PGRI Kokroman Kindergarten, How do parents care for children aged 4-5 years in daily life. This research involved parents, children, older siblings. The method used in this research is a qualitative method and a descriptive approach. Interviews, observation and documentation are all used in data collection methods.